KRITIK SOSIAL DALAM LIRIK LAGU (Social Critics in Songs Lyrics) - Ermitati Ermitati (Salingka, 2015)
AbstractThe Article aims to describe that social criticism not only can be yelled through protest, but also through the lyrics of the song. Social criticism lyrics of the song, in general, addressed to the government, state officials, and Indonesia politicians. The issues discussed in this paper is the social behavior of state officials and politicians in the Orde Baru and Era Reformasi, as well as the vocabulary used by the composer to encode the events that occurred at that time. The data of this paper were collected through listening methods using downloading technique and recording. The data were analyzed with the theory of dynamic model of meaning (Kecskes, 2007), which states that a person’s knowledge of the world may be encoded in the lexical item as a mixture of general knowledge associated with the provision concept, the wordspecific semantic properties (lexicalization knowledge of the world) , and culture-specific conceptual properties. It is something new because during the analysis of social criticism lyrics of the song are dominated by semiotic theory and discourse theory. This paper found four types of behavior of state officials encoded in the lyrics of social criticism, namely (a) the behavior of enriching themselves by corruption the country money, (b) behavior of justifying a variety of ways to get the desired positions, (c) the behavior of being dared to violate religious norms to get the treasure, and (d) the behavior of being happy to commit fornication.Keywords: social critics, behavior, encode, song lyrics, state officialsAbstrakTulisan ini bertujuan untuk mendeskripsikan bahwa kritik sosial tidak hanya dapat dilakukan melalui demonstrasi, tetapi dapat juga dilakukan melalui lirik lagu. Lirik lagu kritik sosial, pada umumnya, ditujukan kepada pemerintah, pejabat negara, dan para politisi Indonesia. Masalah yang dibahas dalam tulisan ini adalah perilaku sosial para pejabat negara dan para politisi pada masa Orde Baru dan Era Reformasi, serta kosakata yang digunakan oleh pencipta lagu untuk menyandikan berbagai peristiwa yang terjadi pada masa itu. Data tulisan ini dikumpulkan melalui metode simak dengan teknik pengunduhan dan teknik pencatatan. Data dianalisis dengan Teori Model Makna Dinamis. Hal itu merupakan sesuatu yang baru karena selama ini analisis lirik lagu kritik sosial didominasi oleh teori semiotik dan teori wacana. Temuan tulisan yaitu empat jenis perilaku pejabat negara yangtersandi dalam lirik lagu kritik sosial, yakni (a) perilaku memperkaya diri dengan cara mengorupsi uang negara, (b) perilaku menghalalkan berbagai cara untuk mendapatkan jabatan yang dinginkan,(c) perilaku berani melanggar norma agama demi mendapatkan harta, dan (d) senang melakukan perbuatan zina.Kata kunci: kritik sosial, perilaku, tersandi, lirik lagu, pejabat negara